Analytical tools for unravelling the metabolism of gas-fermenting Clostridia. (June 2022) - Heffernan, James K; Mahamkali, Vishnu; Valgepea, Kaspar; Marcellin, Esteban; Nielsen, Lars K
Graphical abstract: Highlights: Analytical tools and metabolic models are used routinely in the design gas fermentation processes. Acetogen metabolism is controlled largely at metabolite rather than expression level. Advances in kinetic modelling promises to deliver a deeper understanding of acetogen metabolism and its regulation. Improved analytical techniques for dissolved gasses, tetrahydrofolates and ferredoxins are critical to realise potential. Abstract : Acetogens harness the Wood-Ljungdahl Pathway, a unique metabolic pathway for C1 capture close to the thermodynamic limit. Gas fermentation using acetogens is already used for CO-to-ethanol conversion at industrial-scale and has the potential to valorise a range of C1 and waste substrates to short-chain and medium-chain carboxylic acids and alcohols. Advances in analytical quantification and metabolic modelling have helped guide industrial gas fermentation designs. Further advances in the measurements of difficult to measure metabolites are required to improve kinetic modelling and understand the regulation of acetogen metabolism. This will help guide future synthetic biology designs needed to realise the full potential of gas fermentation in stimulating a circular bioeconomy.